Intervención psicológica en pacientes que deben someterse a un trasplante de médula ósea - Arranz, Pilar; Coca, Cristina; Bayés, Ramón; Rincón, Carola del; Hernández Navarro, Fernando (Psicooncología, 2003)
Bone Marrow Transplantation (BMT) has emerged over the past decade as a new and promising intervention for the Haemato-Oncologic patients or those who have a sensitive tumour to intensive chemotherapy. The application of high-dose of intensive chemotherapy reduces the relapse risk of the illness, increases survival and the possibility of total recovery on the vast majority of cases. However, the patients undergoing this treatment may experience several and multiple potential stressors on long, medium and short term basis. The quality care requires a personal, multidimensional, integral and interdisciplinary approach of these patients and their relatives during the different stages of the treatment. A proposal of a psycho-educational program is presented in order to help patients face the BMT, starting the transplant on the best conditions as possible and facilitating their adaptation during the whole process. This intervention is being realized in the Haematology and Hemotherapy Service on the University Hospital La Paz, Madrid, where 450 patients and their relatives have already participated